Analisis dan Validasi Kinerja Oxygen Analyzer melalui Factory Acceptance Test (FAT) pada Proyek Industri di PT JGC Indonesia - Nada Aqilah Izzatinnisa; Pujianto Pujianto (International Forum of Researchers and Lecturers, 2026)
Operational quality in the oil and gas sector strongly depends on the accuracy of monitoring instruments, such as oxygen analyzers. This study aims to validate the performance of an oxygen analyzer using the Factory Acceptance Test (FAT) procedure conducted by PT JGC Indonesia. The testing methodology involves the use of reference gases at different concentration levels, including nitrogen as the zero gas, to evaluate the linearity and consistency of the analyzer output within the 4-20 mA signal range. In addition, the tests are performed to verify the conformity of the instrument response with the datasheet specifications and applicable FAT procedures. The results show that the analyzer provides accurate measurement data with low deviation and a responsive alarm system under critical conditions. These findings confirm that the instrument meets the required technical standards. Based on the validation results, the oxygen analyzer is considered ready for installation and suitable for operation to support process safety in oil and gas facilities. This achievement confirms that a rigorous validation process is key to ensuring peace and operational safety in the oil and gas industry.